Safety and toxicity of amphotericin B in glucose 5% or intralipid 20% in neutropenic patients with pneumonia or fever of unknown origin: randomised study. Issue 7155 (8th August 1998) - Schöffski, Patrick; Freund, Mathias; Wunder, R; Petersen, D; Köhne, C H; Hecker, H; Schubert, U; Ganser, A
Abstract: Objective : To compare the feasibility of treatment, safety, and toxicity of intravenous amphotericin B deoxycholate prepared in either glucose or intralipid for empirical antimycotic treatment of neutropenic cancer patients. Design : Single centre stratified, randomised non-blinded phase II study. Setting : University hospital providing tertiary clinical care. Subjects : 51 neutropenic patients (leukaemia (35), lymphoma (11), solid tumours (5)) with refractory fever of unknown origin (24) or pneumonia (27). Interventions : Amphotericin B 0.75 mg/kg/day in 250 ml glucose 5% solution or mixed with 250 ml intralipid 20%, given on eight consecutive days then alternate days, as a 1-4 hour infusion. Main outcome measures : Feasibility of treatment, subjective tolerance (questionnaire), and objective toxicity (common toxicity criteria of the National Cancer Institute). Results : Study arms were balanced for age, sex, underlying malignancy, renal and liver function, and pre- and concomitant treatment with antibiotics and nephrotoxic agents. No statistically significant or clinically relevant differences were found between the treatment groups for: daily or cumulative dose and duration of treatment with amphotericin B; incidence and time of dose modifications or infusion duration changes related to toxicity; dose or duration of symptomatic support with opiates, antipyretics, or antihistamines; renal function; subjective tolerance; most common toxicity scores; course of infection; and incidence of treatment failures. Patients treated with amphotericin B in intralipid were given fewer diuretics (P<0.05) and therefore had more peripheral oedema (P<0.01) and needed less potassium supplementation (P<0.05) than patients given amphotericin in glucose. Acute respiratory events were more common in the intralipid arm (P<0.05). Conclusions : Amphotericin B 0.75 mg/kg/day in intralipid given on eight consecutive days then alternate days provides no benefit and is associated with potential pulmonary side effects possibly because of fat overload or an incompatibility of the two drugs.